(untitled) (Journal of the Association for the Study of Australian Literature, 2008)
Taking a cue from Franco Moretti’s research, my article applies statistical methods to probe the history of publishing Australian novels both locally and internationally. By temporarily suspending our discipline’s preoccupation with close readings and canonical judgements, I aim to demonstrate how the computational analysis of large-scale publication data about Australian novels can also provoke alternative kinds of, and responses to, Australian literary history.